Aplikasi Website Pengamanan File Dokumen Menggunakan Kriptografi RSA (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
Data security is something that needs to be considered in maintaining the confidentiality of information, especially those that only contain information that can be known by the authorized party. There are still many cases of data leakage that occur in Indonesia, especially in documents. Documents can be secured using cryptographic techniques. One of the well-known cryptography is RSA Cryptography. The security of RSA cryptography lies in the difficulty of factoring large numbers into prime factors. The implementation of RSA cryptography will be made using the python programming language based on the website. The system created has a success rate of 100% in encrypting documents for each document, and in decrypting it has a success rate of 85% to 96%.